2015
DOI: 10.1155/2015/742658
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Prehypertension with Left Ventricular Mass Assessed by Cardiac Magnetic Resonance Imaging

Abstract: Introduction. The purpose of this observational cross-sectional study was to assess left ventricular mass (LVM) in prehypertensive individuals in comparison to normotensives and to determine if central blood pressure (BP) correlates better with LVM index (LVMI) than brachial BP. Methods and Result. Brachial and central BP measurements were completed at first visit and at 4 weeks in 65 healthy volunteers who were at least 40 years old and not on medication. Subjects were divided into two groups of normotensives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…On the other hand, Mousa et al [10] reported that there was no statistically significant difference in the BMI among the two groups being studied (prehypertensive and normotensive) included in their study.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…On the other hand, Mousa et al [10] reported that there was no statistically significant difference in the BMI among the two groups being studied (prehypertensive and normotensive) included in their study.…”
Section: Discussionmentioning
confidence: 84%
“…also, the mean LVMI in the prehypertension patients was 98.6 ± 8.4 which was statistically significantly higher than the cases with normal BP (66.7 ± 8.7) (p< 0.001). Within the same context, Mousa et al [10] showed that the mean LVMI in the prehypertensive patients was 34.45±7.4 that was statistically significantly higher as compared to the normotensive group (29 ± 6) (p=0.002).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Target organ damage might contribute to future CV events in addition to elevated BP in individuals with prehypertension compared with individuals with optimal BP. Prehypertension has been associated with several types of target organ damage: metabolic syndrome [28,43,44], increased left ventricular mass and left ventricular hypertrophy [44][45][46][47], left ventricular diastolic dysfunction [44,[47][48][49][50], coronary artery calcification [51,52], increased minimum coronary resistance [42], arterial stiffness [32], increased arterial intima-media thickness [53,54], retinal vascular alterations [55], microalbuminuria [56][57][58], hemorheological abnormalities [59], increased tissue plasminogen activator [60], carotid atherosclerosis [61], poor cognitive performance [62], subclinical inflammation [37,63], increased low density lipoprotein (LDL) oxidation in vivo [64], increased serum complement [65], excessive sympathetic response [66], and abnormalities in endothelial progenitor cells [67].…”
Section: The Progression Processmentioning
confidence: 99%